Movement, time, technology, and art - Chau, Christina (Springer, 2020)
Introduction: Peculiar Time; Abstract; 1.1 Movement and Technology for Contemporary Audiences; 1.2 What is Kinetic Sculpture and Kineticism?; 1.3 Exhibiting Kinetic Art; 1.4 Time, Contemporaneity, and Kinetic Art; 1.5 What is Contemporary Art?; 1.6 Talking about time; 1.7 Chapter Outline; References; 2 Revolutions-Forms That Turn; Abstract; 2.1 Revolving, Rotating, Mirroring; 2.2 Cum-Tempore (with Time); 2.3 Avant-Garde Kinetic Artworks at the Biennale; 2.4 Conclusion: Contemporary Exhibition of Modern Kinesis; References; 3 Directions in Kinetic Art: Expanding Spectres of Time. Abstract3.1 Problems with Time and Technology in Art in the 1960s; 3.2 Against Duration: Art and Objecthood; 3.3 Directions in Kinetic Art at the Berkeley Museum (1966); 3.4 Orchestrating Time: Jean Tinguely's Auto-Destructive Machines; 3.5 Conclusion: Technological Expansion and New Durations; References; 4 Systems Aesthetics: A Key Polemic in Contemporary Kinetic Art History; Abstract; 4.1 Key Understandings of Jack Burnham's 'Systems Esthetics'; 4.2 Burnham's Turbulent Relationship with Kineticism; 4.3 Hans Haacke's Kinetic Systems; 4.4 Conclusion: Ontologically Unstable Movement Systems. Moholy-Nagy: New Perceptions of Time and Technological Expansion6.4 Blurring Time with Virtual Volumes; 6.5 Accumulating Temporalities; 6.6 Pioneering a Kinetic a Consciousness of Time; 7 Your Negotiable Panorama: The Seeping Edges of Perceiving Yourself Perceiving; Abstract; 7.1 Frank Popper: From Kinetic to Virtual Art; 7.1.1 Your Negotiable Panorama; 7.2 Intersections with the Virtual: Eliasson, Deleuze and Bergson; 7.3 Deleuze's Crystalline Experiences of Temporality; 7.4 Conclusion: Resensationalising Kinetic Trends; References. Conclusion: Consciousness of Time: Looking Back and Moving ForwardReferences; Index